Synthesis and characterization of biomimetic hydroxyapatite/sepiolite nanocomposites - CHEN, BIQIONG; WAN, CHAOYING (Royal Society of Chemistry, 2011)
Natural fibrous sepiolite with a high surface area, negative surface charge and porous structure is promising for hydroxyapatite (HAp) mineralization since the clay is naturally abundant and biocompatible. In this paper, the use of fibrous sepiolite as a template for growth of HAp nanocrystals was reported for the first time. Carbonated HAp nanorods with dimensions of 20?60 nm in length and 10?20 nm in diameter were successfully grown on the sepiolite surface with a preferred orientation to the c-axis. The critical nucleus radius of HAp in the presence of natural sepiolite was estimated as 0.296?0.312 nm. Strong acid-activation increased the specific surface area of the sepiolite by 205% and also transformed the sepiolite to silica fiber with an elastic modulus being 395% of the original value. The novel HAp/acid-activated sepiolite biocomposite has a specific surface area of 182 m2 g?1 and an elastic modulus of over 20 GPa, considerably higher than those of the HAp synthesized without sepiolite. Such hierarchically assembled HAp/sepiolite biocomposites with controlled size and improved modulus open a new way to expand the applications of naturally abundant clays in biological load-bearing devices.
PUBLISHED
Keywords: Biochemistry; nanocomposites